Mechanisms of Individual Differences in Impulsive and Risky Choice in Rats - Kirkpatrick, Kimberly; Marshall, Andrew T.; Smith, Aaron P. (My University, 2015)
Mechanisms of Individual Differences in Impulsive and Risky Choice in Rats Kimberly Kirkpatrick Department of Psychological Sciences, Kansas State University Andrew T. Marshall Department of Psychological Sciences, Kansas State University Aaron P.
Citation: Kirkpatrick, K., Marshall, A. T., & Smith, A. P. (2015). Mechanisms of Individual Differences in Impulsive and Risky Choice in Rats. Comparative Cognition & Behavior Reviews, 10. Retrieved from http://comparative-cognition-and-behavior-reviews.org/2015/vol10_kirkpatrick_marshall_smith/
Keywords: Impulsive choice; Risky choice; Discounting; individual differences; Rat